دراسة المواد الفعالة والنشاط المضاد للتأكسد والبيولوجي لنبات Azadirachta Indica المتواجد في الجنوب الجزائري - قـاسمــي نيهـاد / بـابــة منـال (university of eloued جامعة الوادي, 2024)
تم إجراء دراسة التركيب الكيميائي النباتي والخصائص البيولوجية لمستخلص أوراق أزاديراشتا إنديكا (النيم) من البيئات القاحلة من خلال تحليل LC-MS، تم تحديد المركبات السائدة في هذا المستخلص كالآتي الكيرسيتين وحمض الأوليانوليك والساليسين والكاتشين كأمثلة على العديد من المركبات النشطة بيولوجيًا في العينة. وكذلك تم تحديد التقدير المحتوى الكلي للفينولات (TPC) والذي تراوحت قيمته (0.159 ± 49.63 (، ومحتوى الكلي للفلافونويدات (TFC) تراوحت قيمته (0.242±12.481 (. أظهر المستخلص القدرة على تثبيط أكسدة β- كاروتين بشكل كبير، بقيمة IC50 تبلغ 0.66 ± 22.29 ، بالإضافة إلى ذلك أظهر المستخلص نشاطًا قويًا مضادًا للأكسدة في اختبار DPPH، بقيمة IC50 تبلغ 0.71 ± 25.01 ، وكان معتدلاً في اختبار ABTS، حيث IC50 بلغت قيمته 45,09 ± 1,23 . كما أظهرت E. coli و P. aeruginosa و S. aureus و B. subtilis حساسية للمستخلص مع تراكيز تتراوح بين VHC و ، مما يدل على أن المستخلص مضاد جيد للميكروبات. بينما تمثل (TP)، (Fs)، (ALT) سلالات الفطريات التي تم اختبار حساسيتها لهذا المستخلص، حيث لوحظت نسب التثبيط من ( إلى )، ( إلى )، ( إلى ) على التوالي، دلت هذه النسب على النشاط القوي المضاد للفطريات لهذا المستخلص. يمكن استنتاج أن مستخلص أوراق Azadirachta Indica من البيئات القاحلة يمتلك أنشطة بيولوجية مهمة يمكن أن تبرر استخدامه التقليدي في الطب والزراعة. A study was conducted on the chemical compound and biological properties of Azadirachta indica (neem) leaf extract from arid environments through LC-MS analysis. Predominant compounds of this extract, such as Quercetin, Linoleic Acid, Salicin, and Catechin, have been identified to serve as examples of many biologically active compounds in this sample. The extract showed a significant ability to inhibit β-carotene oxidation, with an IC50 value of . Additionally, it revealed strong antioxidant activity in the DPPH test, with an IC50 value of , and moderate activity in the ABTS test, where the IC50 value was Correspondingly, the total content estimation of phenols (TPC) has been identified to be between , and the total flavonoids content (TFC) is between Moreover, it showed sensitivity against E. coli, P. aeruginosa, S. aureus, and B. subtilis with concentrations ranging from VHC to , indicating its antimicrobial properties. (TP), (Fs), and (ALT) represent the fungal strains that were tested for extract sensitivity, and inhibition percentages were observed respectively ranging from (76.47% to 89.88%), (70.58% to 89.88%), and (87.71% to 90.57%). The percentages indicate the extract’s potent antifungal activity. In conclusion, Azadirachta indica leaf extract from arid environments possesses crucial biological activity that potentially may justify its traditional usage in medicine and agriculture.
مدكرة ماستر كيمياء
Keywords: التركيب الكيميائي النباتي، أزاديراشتا إنديكا، النيم، مضاد للأكسدة، مضاد للميكروبات، مضاد للفطريات.; Azadirachta Indica; Neem; phytochemical compounds; antioxidant activity; antimicrobial activity; antifungal activity